Influence of Diosmin Treatment on the Level of Oxidative Stress Markers in Patients with Chronic Venous Insufficiency. (28th August 2018) - Feldo, Marcin; Woźniak, Michał; Wójciak-Kosior, Magdalena; Sowa, Ireneusz; Kot-Waśik, Agata; Aszyk, Justyna; Bogucki, Jacek; Zubilewicz, Tomasz; Bogucka-Kocka, Anna
Abstract : Oxidative stress plays an important role in the pathophysiology of many human disorders, while antioxidants prevent the development of various adverse symptoms. Diosmin is a natural flavonoid applied in vascular system disorders, especially in chronic venous insufficiency (CVI), and it plays a significant part in the alleviation of CVI symptoms. Due to antioxidant activity, it also has the ability to scavenge the oxygen free radicals and hence decreases the level of oxidative stress biomarkers, such as prostaglandins and their precursors—isoprostanes. In the study, the influence of diosmin treatment on the level of isoprostanes in plasma samples of patients suffering from CVI was examined. The qualitative analysis was performed using high-performance liquid chromatography with spectrometry detection (LC-MS). The statistically significant decrease of isoprostane content after 3 months of treatment was observed within the studied group; however, the most significant changes were observed in patients who smoke.